International Conference on Maintenance Dredging II proceedings of the International Conference on Maintenance Dredging, organised by the Institution of Civil Engineers and held in Bristol, UK, on 6-7 May 2004. (Thomas Telford, 2005)
Presents the proceedings of the 2nd International Conference on Maintenance Dredging in May 2004. This work aims to provide several aspects of maintenance dredging including regulation dredging methods, dredged material treatment and beneficial use contract management, and environmental impact assessment and mitigation.